Development and evaluation of a ward-based clinical pharmacy service on a neonatal intensive care unit (NICU). Issue 2 (12th March 2012) - Conway, C.; Conyard, E.; Lynch, R.
Abstract : Background: Several international documents highlight the benefits of ward-based clinical pharmacy services. The 2007 NPSA document 'Safety in doses – Medication incidents in the NHS' indicates that serious medication errors may be three times more common among children than in adults. Therefore a clinical pharmacy service was piloted on the 16-bedded NICU. Purpose: To evaluate the clinical significance of interventions made by a pharmacist on 'medicines management' and assess the perceptions of healthcare professionals. Objectives: Literature review Develop a clinical pharmacy Standard Operating Procedure for NICU. Implement a clinical pharmacy service; evaluate clinical significance and level of risk of interventions. Evaluate the perceptions of healthcare professionals on NICU to new service. Recommend on future clinical pharmacy requirements in NICU. Materials and methods: The pharmacist attended the NICU to review prescriptions in accordance with a predefined SOP over a three month period. Activities were categorised into interventions* and other activities. All interventions were assessed by a clinical pharmacist for both clinical significance and level of risk. A random sample of these interventions was also assessed by a NICU/PICU pharmacist and a consultant neonatologist for validation. An anonymous questionnaire was circulated to healthcare professionals in the NICU to assess their perception of the new service. * An intervention was defined as any recommendation made by a pharmacist with the intent to change treatment or monitoring. Results: 110 patients were reviewed and 73 interventions made; the incidence rate for interventions was 5.4/100 patient care days and 9.1/100 reviewed prescriptions. Dosing errors accounted for 47.9% of all interventions. Over 69% of the interventions were considered significant and 11.1% very significant. The clinicians' acceptance rate of the interventions was 91.8%. The majority of responders to the questionnaire agreed that the presence of the ward pharmacist improved medication safety and the quality of care. Conclusions: The clinical significance of the interventions made demonstrates the requirement for a permanent specialist clinical pharmacist in the NICU.